Evaluation of an Integrated Telemonitoring Surveillance System in Patients with Coronary Heart Disease - Ammenwerth, E.; Woess, S.; Baumgartner, C.; Fetz, B.; van der Heidt, A.; Kastner, P.; Modre-Osprian, R.; Welte, S.; Poelzl, G. (Methods of Information in Medicine, 2015)
Objectives: Cardiovascular diseases are the most frequent cause of death in industrialized countries. Non-adherence with prescribed medication and recommended lifestyle changes significantly increases the risk of major cardiovascular events. The telemonitoring programme MyCor (Myokardinfarkt und Koronarstent Programm in Tirol) is a multi-modal intervention programme to improve lifestyle and medication management of patients with coronary heart disease (CHD). It includes patient education, self-monitoring with goal-setting and feedback, and regular clinical visits. We evaluated the MyCor telemonitoring programme regarding technical feasibility, user acceptance, patient adherence, change in health status, and change in quality of life.Methods: A 4½-month study was conducted with two telemonitoring phases and one interim phase. The study comprised patient surveys, standardized assessment of quality of life using the MacNew questionnaire at study entry and after 4 and 18 weeks, analysis of adherence to medication and physical activity during the two telemonitoring phases, and analysis of reached goals regarding health conditions during the telemonitoring phases.Results: Twenty-five patients (mean age: 63 years) participated in the study. Patients showed a high acceptance of the MyCor tele-monitoring programme. Patients reported feelings of self-control, motivation for lifestyle changes, and improved quality of life. Adherence to daily measurements was high with 86% and 77% in the two telemonitoring phases. Adherence to medication was also high with up to 87% and 80%. Pre-defined goals for physical activity were reached in up to 86% and 73% of days, respectively. Quality of life improved from 5.5 at study entry to 6.3 at the end (p< 0.01; MacNew questionnaire). Reductions in blood pressure and heart rate or an improvement in reaching defined goals could not be observed.Conclusions: The MyCor telemonitoring programme Tirol for CHD patients has a high rate of acceptance among included patients. Critical evaluation revealed subjective benefits regarding quality of life and health status as well as high adherence rates to medication and lifestyle changes. Achieving long-term adherence and verifying clinical outcomes, however, remains an open issue. Our findings will promote further studies, addressing different strategies for an optimal mix of patient education, telemonitoring, feedback, and clinical follow-ups.
Keywords: Medical informatics; evaluation studies; cardiovascular diseases; myocardial infarction; blood pressure monitoring; patient empowerment; medication adherence